THE ECONOMIC ACCOUNTING APPROACH. - Lazenby, C. D. (The Accounting Review, 1927)
Abstract According to the article author, the term "bookkeeping approach," is a misnomer. Much more is involved than the term implies. It should be called the accounting foundation, without which no real worthwhile accounting superstructure can ever be built. The subject of bookkeeping approach really resolves itself into a question of bookkeeping method. Book-keeping method and pedagogy constitute the "open forum" in commercial work today. There is an increasing feeling among book- keeping teachers that "all is not well in educational Egypt." Many of the most progressive teachers are realizing that we have never got to first base in the development of a mound bookkeeping pedagogy. Bookkeeping is to-day an acknowledged factor in secondary education. It has acquired its present permanent footing in the face of determined criticism and opposition on the part of many educators. And very few subjects have in so short a time obtained such a firm and universal footing in high school curricula. In the beginning, the high school Inherited the textbooks, the teachers, and the methods of the business college. Measured by present educational standards, all of these were extremely inadequate. Thanks to a number of conditions, the teaching element has greatly improved.